2020
DOI: 10.21037/qims.2020.02.15
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography characterizes the roughness and thickness of the heterogeneous layer on cortical bone surface induced by Er:YAG laser ablation at different moisture contents

Abstract: Background: As an innovative bone ablation tool, pulsed erbium: yttrium-aluminum-garnet (Er:YAG) laser is being used in clinical practice. It faces the same problems as traditional tools: the water content of bone usually changes with the position, while the amount of water spray in the process of laser irradiation is also uncertain. Real-time monitoring of the effects of laser bone ablation is necessary, but effective tools are still lacking. In this study, we examined the feasibility of rapidly and non-destr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Twenty locations on each OCT image of Rabbits #1 and #2 were randomly selected, and the light signal reflection/scattering bright band thickness of the enamel layer and dentin layer of each tooth was measured according to the change of light intensity. Baseline calibration was performed on each surface line of the selected locations, and the surface roughness of the sample was measured according to the arithmetic mean of the absolute value of the distance between each point on the sample surface and the baseline [23]. The surface roughness and the differences of changes in the light signal reflection/scattering bright band thickness of the enamel layer and dentin layer were subjected to one-way analysis of variance (ANOVA) followed by the Bonferroni post hoc test for multiple comparisons at a 5% significance level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty locations on each OCT image of Rabbits #1 and #2 were randomly selected, and the light signal reflection/scattering bright band thickness of the enamel layer and dentin layer of each tooth was measured according to the change of light intensity. Baseline calibration was performed on each surface line of the selected locations, and the surface roughness of the sample was measured according to the arithmetic mean of the absolute value of the distance between each point on the sample surface and the baseline [23]. The surface roughness and the differences of changes in the light signal reflection/scattering bright band thickness of the enamel layer and dentin layer were subjected to one-way analysis of variance (ANOVA) followed by the Bonferroni post hoc test for multiple comparisons at a 5% significance level.…”
Section: Discussionmentioning
confidence: 99%
“…Immediately after every preparatory step, the specimens of Rabbits #1 and #2 were scanned by an OCT system (as it was shown in Figure 1A) in our medical imaging innovation laboratory that was described in the previous study [23] and was observed and recorded under an SM (Leica, Wetzlar, Germany) at 35 magnifications. The OCT system used 840 nm central wavelength (λ), 40 nm bandwidth (∆λ), 5 MW power (P), and 7.24 µm axial resolution.…”
Section: Oct Scanning Imaging and Sm Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…3,6 The use of erbium lasers for performing procedures that require bone tissue removal has been proposed by several authors, and it is possible to use this wavelength to perform precise sections, with minimal damage to adjacent tissues. [17][18][19][20] The use of lasers in osteotomies could reduce the level of trauma and contamination during the procedure, since the device is working effectively at a distance from the target tissue, which can lead to an improvement in the tissue network. 17 The erbium laser used in this case report was efficient in performing the osteotomy, although some studies have shown that the surgery time can be longer with the use of a laser.…”
Section: Case Reportmentioning
confidence: 99%
“…189 The results from their study showed that OCT could quickly and accurately evaluate the differences between the moisture content, as compared to histology and scanning electron microscope (SEM). 233 NaYF 4 :Yb, Er@CaF 2 nanoparticles with a small size (10-13 nm) robustly enhance (ca. 300 times) upconversion emission compared with the pristine nanoparticles.…”
Section: Lanthanum and Other Re Metal-doped Nanobiomaterialsmentioning
confidence: 99%